Isolation of a Rhodobacter capsulatus mutant that lacks c-type cytochromes and excretes porphyrins. - Biel, S W (1990)
A Rhodobacter capsulatus mutant lacking cytochrome oxidase activity was isolated by Tn5 mutagenesis. Difference spectroscopy of crude extracts and extracted c-type cytochromes demonstrated that this mutant completely lacked all c-type cytochromes. The strain did, however, synthesize normal amounts of b-type cytochromes and nonheme iron. This mutant also excreted large amounts of coproporphyrin and protoporphyrin and synthesized reduced amounts of bacteriochlorophyll, suggesting a link between the synthesis of c-type cytochromes and the expression of the tetrapyrrole biosynthetic pathway.